Aparelho de baropodometria para uso na reabilitação de alterações de marcha - Scremim, Reginato Domingos (2012)
The neuro-motor changes can reduce the movements, activities of daily living and social life. Within these changes are the dyspraxia or apraxia of movements that can unbalance the voluntary movement, especially of the ankle muscles and develop a stiffness of movement known as "equinus foot". The equinus foot decreases the heel support and consequently the balance control of the body making it difficult to walking properly. As a source of help to people affected by this problem, we developed a device called Baropodometer that uses the concept of biofeedback, providing audiovisual information in order to stimulate and or correct the absence of heel strike on the ground assisting in the realization and correction of balance and gait. The device reads the pressure applied by the front and rear part of the foot on the ground by means of sensors placed in insoles and accommodated in shoes (e.g., sandals). This action is translated visually through numbers shown in displays and columns of LEDs that are illuminated according to the increase of the pressure on the sensors, as well as an audio signal with variable frequency and adjustable volume produced by an internal buzzer. The device can store the collected data in a memory card that can be read on a microcomputer, allowing creation of tables and graphs for further analysis enabling the planning of rehabilitation action. With the help of a method of rehabilitation, the device was clinically validated with the participation of ten volunteers who achieved an excellent result (i.e, all patients after 10 sessions were able to properly support the equinus foot) showing that the rehabilitation is possible with the use of the developed device.